2014
DOI: 10.1142/s0218216514500072
|View full text |Cite
|
Sign up to set email alerts
|

Walks along braids and the colored Jones polynomial

Abstract: Abstract. Using the Huynh and Lê quantum determinant description of the colored Jones polynomial, we construct a new combinatorial description of the colored Jones polynomial in terms of walks along a braid. We then use this description to show that for a knot which is the closure of a positive braid, the first N coefficients of the N -th colored Jones polynomial are trivial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…On the other hand, when p > 1, K p ,0 (q) is not modular of any weight, according to K. Ono. This disproves any conjectured modularity properties of 0 (q), even for 5 2 . On the other hand, …”
Section: Table 5 Twist Knotssupporting
confidence: 76%
See 2 more Smart Citations
“…On the other hand, when p > 1, K p ,0 (q) is not modular of any weight, according to K. Ono. This disproves any conjectured modularity properties of 0 (q), even for 5 2 . On the other hand, …”
Section: Table 5 Twist Knotssupporting
confidence: 76%
“…The zero stability is also proven independently by Armond for all adequate links [1], which include alternating links and closures of positive braids, see also [2]. The advantage of our approach is that it proves stability to all orders and gives explicit formulas (in the form of generalized Nahm sums) for the limiting series, which in particular implies convergence in the open unit disk in the q-plane and allow for the study of their redial asymptotics.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…This can be used to prove various q-identities and it was first utilized by Armond and Dasbach in [2] where they showed that the Andrews-Gordon identity for the theta function can be proven using two methods to compute the of the tail of the (2, 2k + 1) torus knots. In particular Armond and Dasbach use R-matrices and a combinatorial version of the quantum determinant formulation of Huynh and Le [10] developed by Armond [4] to compute the colored Jones polynomial of the (2, 2k + 1) torus knot. These computations are then used to obtain two expressions of the tail associated with the (2, 2k + 1) torus knot.…”
Section: By Assumption We Have Tγmentioning
confidence: 99%
“…In [1] it was shown that for a knot K , which can be expressed as the closure of a positive braid, T K .q/ D 1. In [3] Abhijit Champanerkar and Ilya Kofman show this for a knot expressed as a positive braid with a full twist, and also determine a sequence of coefficients beyond the first N .…”
Section: Introductionmentioning
confidence: 99%